Kajian Mengenai Konteks dan Strategi Pembelajaran yang Relevan bagi Taman Kanak-Kanak Dharma Wanita Kalasey Satu, Minahasa - Marde Christian Stenly Mawikere; Sudiria Hura (Institut Agama Kristen Negeri Manado, 2021)
This article is a Study of Learning Contexts to Suggest Relevant Learning Strategies for Taman Kanak-Kanak Dharma Wanita Kalasey Satu, Minahasa. This study was conducted using a descriptive method through literature approach and empirical research related to the context and strategies of early childhood learning. The results of the study show that there are various learning contexts that are oriented towards children as educational subjects as well as various learning strategies that emphasize the role of the teacher as a facilitator in teaching and the participation of children as learners. Therefore, the PAUD unit studied, namely TK Dharma Wanita Kalasey Satu, was able to take advantage of several learning strategies that were relevant to the learning context, especially during this pandemic.